2015
DOI: 10.1002/ep.12261
|View full text |Cite
|
Sign up to set email alerts
|

Power improvement of enzymatic fuel cells used for sustainable energy generation

Abstract: Poly(3‐thiopheneacetic acid‐co‐3‐methylthiophene) conductive polymer was electrosynthesized with ferrocene and used for an enzymatic fuel cell including glucose oxidase and bilirubin oxidase enzymes. The system was operated in a single‐compartment and membrane‐less cell by using glucose as fuel. Detailed optimization ensured to achieve considerable power output to generate sustainable energy from municipal wastewater as a renewable fuel source. Maximum power density of 1 μW/cm2 was generated at a cell voltage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Increasing current up to 20 cycle can be attributted to the increasing carboxyl groups of the intensified copolymer with increasing electropolymerization duration, because these groups provide more capacity for chemical enzyme immobilization. The current decrase beyond 20 cycle indicated that the surface of the film was too dense, and as a result of this, pyruvate and phosphate diffusions and also electron transport on the surface were limited . Optimum duration for electropolymerization was set as 20 cycle for the generation of the improved signals for phosphate measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing current up to 20 cycle can be attributted to the increasing carboxyl groups of the intensified copolymer with increasing electropolymerization duration, because these groups provide more capacity for chemical enzyme immobilization. The current decrase beyond 20 cycle indicated that the surface of the film was too dense, and as a result of this, pyruvate and phosphate diffusions and also electron transport on the surface were limited . Optimum duration for electropolymerization was set as 20 cycle for the generation of the improved signals for phosphate measurements.…”
Section: Resultsmentioning
confidence: 99%
“…This situation creates a blocking effect on the electron transport mechanism from the enzyme to the electrode 35 . However, the increased polymer density provides a large surface area for the immobilization of higher amounts of enzymes, which makes the EFC more powerful 36 . Therefore, polymeric film density on the both bioanode and biocathode should be optimized to acquire maximum performance from the EFC.…”
Section: Resultsmentioning
confidence: 99%
“…33 In our previous studies, the potential of BOD immobilized biocathodes constructed with different designs was optimized and found to be +0.36 V for maximum power generation. [34][35][36][37] Therefore, the operational potential of +0.36 V was used for the BOD immobilized biocathode side of the designed EFC.…”
Section: Determination Of the Bioanode Voltagementioning
confidence: 99%
See 1 more Smart Citation
“…Many reports show the use of polythiophenes and their derivatives in chemical enzyme immobilization. For example, Korkut et al have enhanced the power density of the EFC by the improvement of conductivity of poly(3-thiophene acetic acid) (PTAA) by copolymerization with alkyl thiophenes, which is followed by modification with a ferrocene mediator for electron transfer rate improvement [95]. Therefore, polythiophenes can be good candidates as a polymeric matrix in enzyme immobilization because of the presence of carboxylic functional groups and their good conductivity.…”
mentioning
confidence: 99%